A82 SUCCESSFUL RESECTION OF GRADE 1 DUODENAL NEUROENDOCRINE TUMOURS USING ENDOSCOPIC TECHNIQUES IN TWO CANADIAN HOSPITALS - Klemm, N K (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Given the rarity of duodenal neuroendocrine tumours (dNETs), limited guidelines exist for resection of well-differentiated, ≤10 mm dNETS. As incidence rises, alternatives to surgery are valuable. We present 9 cases of endoscopic dNET resections and a literature review. AIMS: To demonstrate efficacy and safety of endoscopic resection for dNETs ≤10 mm at 2 Canadian hospitals. METHODS: We retrospectively analyzed data on 7 patients that had endoscopic dNET resection from 2013–2018. Endoscopic resection occurred if dNETs were ≤10 mm in diameter, did not extend to the muscularis propria and lymphovascular invasion was absent. WHO 2017 classification was used. RESULTS: All patients had biopsies and 5 (71%) had EUS prior to resection; 4 females and 3 males underwent resection of 9 dNETs; 2 via cap-assisted snare polypectomy; 4 with cap-assisted band mucosectomy; and 2 over-the-scope clip-assisted resection. The median size was 10 mm (4–11); 6 (67%) dNETS were found in the duodenal bulb, 2 at the D1/D2 junction and 1 in D2 alone. The median age was 68.5 (50–79) years. All dNETs were submucosal and well-differentiated. The dNETs were resected en bloc, but 3 did not have clear margins. Two procedures were complicated by duodenal perforation; 1 requiring surgery and 18 days in hospital. One case was complicated by bleeding with successful endoscopic hemostasis. The majority (75%) of resections were day procedures. Patients were followed for 6–12 months with an EGD or chromogrannin A. None of the patients had endoscopic residual disease, but 1 patient required a second procedure to remove a dNET left in situ following the initial resection of 2 dNETs 12 months earlier. In our literature review of 178 patients, the majority of dNETs were resected by EMR 81% (150/185) versus ESD, similar to our experience. Patients were slightly younger with a mean age of 63.28, and most dNETs (46%) were found in the duodenal bulb. Complications included intraoperative bleeding, perforation and death in 17 (9.55%), 9 (5.06%) and 1 (0.06%) patient(s) respectively. The rate of recurrence was 4/178 (2.25%) and patients had a mean follow up of 26.1 months. CONCLUSIONS: Well-differentiated dNETs ≤10 mm in diameter can be successfully resected endoscopically. Complications can be managed intraoperatively and hospital stay remains minimal. FUNDING AGENCIES: None